A vadon titka - St. John, Patricia Mary, 1919-1992.; Mills, Mary; Rees, Gary (Budapest : Evangéliumi K., 2006)
While living with her aunt in the English countryside, a naughty nine-year-old girl named Ruth finds her life changed when she asks the Good Shepherd, Jesus, to come to her.
Original title: The Tanglewoods' secret.
HU OSA 430 - Donation of Zsuzsa Horváth
Keywords: Christian life -- Fiction; Aunts -- Fiction; England -- Fiction